The Akt inhibitor KP372-1 inhibits proliferation and induces apoptosis and anoikis in squamous cell carcinoma of the head and neck - Mandal, Mahitosh (2006)
Therapies that target signaling pathways critical to the pathogenesis and progression of squamous cell carcinoma of the head and neck (HNSCC) are needed. One such target, phosphatidylinositol 3-kinase, and its downstream target serine/threonine kinase, Akt, are up-regulated in HNSCC. Targeted therapy could consist of inhibitors of these kinases or, alternatively, of inhibitors of the pathways that they regulate. To explore the effect of Akt inhibition on the growth and survival of HNSCC tumors, we evaluated the effect of a novel Akt inhibitor, KP372-1, on the growth, survival, and sensitivity to anoikis of HNSCC cell lines in culture. Using Western blotting of head and neck cancer cell lines and squamous mucosa and carcinoma specimens, we found that Akt was highly phosphorylated in head and neck cancer cell lines and human head and neck squamous carcinoma specimens. Treatment of HNSCC cell lines with KP372-1 blocked the activation of Akt, inhibited head and neck cancer cell proliferation, and induced apoptosis and anoikis in several HNSCC cell lines. Furthermore, KP372-1 decreased the phosphorylation of the S6 ribosomal (Ser240/244) protein, which is a downstream target of Akt. Taken together, these findings indicate that KP372-1 may be a useful therapeutic agent for HNSCC and should be further evaluated in preclinical models of HNSCC.